2015
DOI: 10.18632/oncotarget.4312
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastasis risk and patterns of nasopharyngeal carcinoma in the era of IMRT: long-term results and benefits of chemotherapy

Abstract: Purpose: To report the distant metastasis (DM) risk and patterns for nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiotherapy (IMRT) and to analyze the benefits of chemotherapy based on DM risk.Materials and Methods: 576 NPC patients were analyzed. The DM rates were calculated using the Kaplan-Meier method, and the log-rank test was used to compare differences. The patients were divided into different risk subclassifications according to DM hazard ratios.Results: 91 patients developed DM af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 30 publications
4
74
0
1
Order By: Relevance
“…In recent years, intensity-modulated radiotherapy (IMRT) has replaced 2D-CRT as the first choice for the treatment of NPC. A large number of studies (Lee et al 2014, Su et al 2011Wang et al 2014;Li et al 2015) have shown that the 5-year loco-regional control rate has increased substantially to reach approximately 90% in NPC patients treated by IMRT with or without chemotherapy, but the distant metastasis rate remains high (14-26%) with no clear improvement in OS (77-84%). Thus, the treatment of NPC remains challenging, and it is of vital importance to identify factors that can predict the prognosis of NPC patients before IMRT to provide individual comprehensive therapy and improve treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, intensity-modulated radiotherapy (IMRT) has replaced 2D-CRT as the first choice for the treatment of NPC. A large number of studies (Lee et al 2014, Su et al 2011Wang et al 2014;Li et al 2015) have shown that the 5-year loco-regional control rate has increased substantially to reach approximately 90% in NPC patients treated by IMRT with or without chemotherapy, but the distant metastasis rate remains high (14-26%) with no clear improvement in OS (77-84%). Thus, the treatment of NPC remains challenging, and it is of vital importance to identify factors that can predict the prognosis of NPC patients before IMRT to provide individual comprehensive therapy and improve treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic value of PNI has rarely been investigated in NPC patients. Furthermore, the TNM staging system is the most important tool for predicting prognosis and guiding the NPC treatment strategy, but the heterogeneity of patients with different risk factors in the same stage has limited the ability of this system to distinguish patients with different prognoses and make accurate treatment choices (Su et al 2011;Li et al 2015). Therefore, it is necessary to identify other prognostic factors that can help predict the prognosis and aid in the treatment of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to the clinical and biological behavior of NPC patients following chemoradiotherapy, NPC was subdivided into four types: type I (no primary and regional recurrence and no distant metastasis), type II (primary or regional recurrence and no distant metastasis), type III (no primary and regional recurrence and distant metastasis), and type IV (primary or regional recurrence and distant metastasis) 3. In the intensity-modulated radiation therapy era, distant metastasis was observed as treatment failure in NPC, and the most frequent type was bone metastasis 4. Some scholars have suggested subdividing the M1 stage of NPC and providing a more individualized therapy 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the effect of 2DCRT herein was in fact the combined one of 2DCRT and intracavitary intubation or radiotherapy boost. As reported by Li et al [21], IMRT had the same distant metastatic timing and distribution as 2DCRT, and consequently it had limited contribution to distant control in NPC. In combination, IMRT was not unexpected to achieve equivalent survival outcomes to 2DCRT, as showed in the present study.…”
Section: Discussionmentioning
confidence: 74%